Prevention of Cardiac Hypertrophy by the Use of a Glycosphingolipid Synthesis Inhibitor in ApoE−/− Mice - Mishra, Sumita (Biochem Biophys Res Commun, 2015)
ApoE−/− mice fed a high fat and high cholesterol (HFHC) diet (20% fat and 1.25% cholesterol) from 12 weeks of age to 36 weeks revealed an age-dependent increase in the left ventricular mass (LV mass) and decline in fractional shortening (FS%), which worsened with HFHC diet. These traits are indicative of maladaptive pathological cardiac hypertrophy and dysfunction. This was accompanied by loading of glycosphingolipids and increased gene expression of ANP, BNP in myocardial tissue. Masson’s trichrome staining revealed a significant increase in cardiomyocyte size and fibrosis. In contrast, treatment with 5 and 10 µM D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP), an inhibitor of glucosylceramide synthase and lactosylceramide synthase, dose-dependently decreased the load of glycosphingolipids and preserved fractional shortening and maintained left ventricular mass to normal 12-week-old control levels over a 6 month treatment period. Our mechanistic studies showed that D-PDMP inhibited cardiac hypertrophy by inhibiting the phosphorylation of mitogen–activated protein kinase (MAPK). We propose that associating increased glycosphingolipid synthesis with cardiac hypertrophy could serve as a novel approach to prevent this phenotype in experimental animal models of diet -induced atherosclerotic heart disease.